ANALISIS PENERAPAN AKUNTANSI PEMBIAYAAN IJARAH BERDASARKAN PSAK NOMOR 107 PADA PT BANK RAKYAT INDONESIA SYARIAH CABANG LHOKSEUMAWE - Falahuddin, Falahuddin; Aprilia, Icut (Jurnal Akuntansi dan Keuangan, 2017)
This study aims to analyze the application of Ijarah financing accounting based on PSAK No.107 at PTÂ  Bank Rakyat Indonesia Syariah, Branch of Lhokseumawe. The data used in this study are qualitative data which is obtained by conducting interviews with the parties concerned. The data analysis method used in this study is a qualitative descriptive method. Based on the results of the study, it is known that the financing system of Ijarah Muntahiyya Bittamlik at PT Bank Rakyat Indonesia Syariah, Branch of Lhokseumawe is in accordance with the generally accepted accounting principles for sharia banking, namely PSAK 107 concerning the application of Ijarah financing.